Comprehensive Mutation Analysis of the CYP21A2 Gene: An Efficient Multistep Approach to the Molecular Diagnosis of Congenital Adrenal Hyperplasia - Xu, Zhi (J Mol Diagn, 2013)
Congenital adrenal hyperplasia, due to 21-hydroxylase deficiency (21-OHD) is an autosomal recessive disorder of adrenal steroidogenesis caused by mutations in the CYP21A2 gene. Direct comparison of established and novel methodologies of CYP21A2 genetic analysis in a large cohort representing a wide range of genotypes has not been previously reported. We genotyped a cohort of 129 unrelated patients with 21-OHD, along with 145 available parents, using Southern blot (SB) analysis, multiplex ligation-dependent probe amplification (MLPA), PCR-based restriction fragment length polymorphism (RFLP) analysis, multiplex minisequencing and conversion-specific PCR, duplication-specific amplification, and DNA sequencing. CYP21A2 genotyping identified four duplicated CYP21A2 genes (1.53%) and 79 chimeric CYP21A1P/CYP21A2 genes (30.15%). Parental SB data were essential for determining the CYP21 haplotype in three cases, whereas PCR-based RFLP analysis was necessary for MLPA results to be accurately interpreted in the majority of cases. The comparison of different methods in detecting deletion and duplication showed that MLPA with PCR-based RFLP was comparable with SB analysis, with parental data of 100% sensitivity and specificity. DNA sequencing was required for the identification of 16 (6.1%) rare point mutations and determination of clinically significant chimera junction sites. MLPA with PCR-based RFLP analysis is an excellent substitute for SB analysis in detecting CYP21A2 deletion and duplication and a combination of MLPA, PCR-based RFLP, duplication-specific amplification, and DNA sequencing is a convenient and comprehensive strategy for mutation analysis of the CYP21A2 gene in patients with 21-OHD.